The complete mitochondrial genome of the pear pyralid moth, Euzophera pyriella Yang. Issue 1 (1st January 2017) - Yang, Minglu; Feng, Shiqian; Cao, Yu; Han, Xu; Xiong, Renci; Li, Zhihong
Abstract: The pear pyralid moth, Euzophera pyriella Yang, is an important fruit pest in Xinjiang, China. Here, we report the complete mitochondrial genome of E. pyriella which was 15, 184 bp and composed of 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes, and a control region. 21 genes were in majority strand and 16 genes were in minority strand. ATG, ATT, CGA, GAT were initiation codons and TAA, TA, T were termination codons. The tRNA genes ranged in length from 63 to 72 bp. The length of 12S and 16S rRNA genes were 773 and 1330 bp, respectively. The species belong to the family Pyralidae and have a closer relationship according to the phylogenetic analyses.